2021
DOI: 10.3389/fcimb.2021.657775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Liposomal Glutathione in Altering the Immune Responses Against Mycobacterium tuberculosis and the Mycobacterium bovis BCG Strain in Individuals With Type 2 Diabetes

Abstract: The World Health Organization (WHO) has identified type 2 diabetes (T2DM) as a neglected, important, and re-emerging risk factor for tuberculosis (TB), especially in low and middle-income countries where TB is endemic. In this clinical trial study, oral liposomal glutathione supplementation (L-GSH) or placebo was given to individuals with T2DM to investigate the therapeutic effects of L-GSH supplementation. We report that L-GSH supplementation for 3 months in people with T2DM was able to reduce the levels of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…In addition, in vitro M. tb survival and growth in infected PBMCs from T2DM patients is significantly increased compared to healthy controls [17]. Similar to previous studies performed with HIV-positive patients, supplementation with a liposomal formulation of GSH in T2DM subjects restored GSH levels and consequently decreased oxidative stress, modulated a Th-1 cytokine response to M. tb, and enhanced in vitro granuloma formation and M. tb control [8,[17][18][19]. Altogether, these studies suggest that GSH fills important immunomodulatory roles in granuloma formation and in the control of M. tb growth in vitro.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, in vitro M. tb survival and growth in infected PBMCs from T2DM patients is significantly increased compared to healthy controls [17]. Similar to previous studies performed with HIV-positive patients, supplementation with a liposomal formulation of GSH in T2DM subjects restored GSH levels and consequently decreased oxidative stress, modulated a Th-1 cytokine response to M. tb, and enhanced in vitro granuloma formation and M. tb control [8,[17][18][19]. Altogether, these studies suggest that GSH fills important immunomodulatory roles in granuloma formation and in the control of M. tb growth in vitro.…”
Section: Introductionmentioning
confidence: 96%
“…Patients with T2DM also have an increase in proinflammatory cytokines and an inadequate Th-1 effector response [16]. Peripheral blood mononuclear cells (PBMCs) isolated from T2DM patients showed an impaired ability to form granulomas in vitro when infected with Erdman strain M. tb compared to isolates derived from healthy patients [15,17]. In addition, in vitro M. tb survival and growth in infected PBMCs from T2DM patients is significantly increased compared to healthy controls [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the studies were focused on mycobacteria antigens, including several mycobacterial strains such as M. tb H37Rv [ 5 , 22 , 27 , 28 , 38 , 39 , 43 , 44 , 45 , 47 , 49 , 50 , 55 , 66 , 71 , 72 , 73 , 74 , 75 , 76 ], M. tb Erdmann [ 63 , 65 , 77 , 78 ], and species such as M. leprae [ 12 , 79 ], M. abscessus [ 48 ] as well as BCG [ 24 , 29 , 30 , 56 , 57 , 62 , 69 , 80 ] and PPD [ 23 , 54 , 59 , 61 ]. Others used antigens of other infectious species such as Schistosoma [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 58 ] or Candida [ 2 , 26 , 42 , 81 ].…”
Section: Infobox: Important Technical Considerationsmentioning
confidence: 99%
“…Along with diminished GSH, T2DM patients have an increase in levels of proinflammatory cytokines and MDA, a by-product of lipid peroxidation and measurement for oxidative stress (Guerra et al, 2012;Lagman et al, 2015;Teskey et al, 2018a). Previous studies have reported that when infected in vitro with M. tb Erdman strain, the peripheral blood mononuclear cells (PBMCs) from T2DM patients had impaired granuloma formation that is permissive for increased survival and growth of M. tb, compared to the PBMCs from healthy individuals (Teskey et al, 2018b;To et al, 2021). However, these effects were reversed when the infected cells were supplemented with L-GSH.…”
Section: Introductionmentioning
confidence: 99%